Treatment expectations of patients and clinicians: a cross-sectional study - Li, Jiarui; Xiao, Chunfeng; Li, Tao; Duan, Yanping; Jiang, Yinan; Shi, Lili; Hong, Xia; Geng, Wenqi; Hu, Jiaojiao; Wang, Yufei; Dai, Bindong; Cao, Jinya; et al. (Frontiers in Psychiatry, 2024)
Importance Understanding treatment expectations of patients and their clinicians is of great importance in improving personalized medical services and enhancing patient safety systems. Objective To investigate treatment expectations of patients and their clinicians and compare differences between both, by using a pair of validated structured assessment tools covering three key aspects/dimensions of clinical interests. Design, setting, and participants This single-center cross-sectional study was conducted at Peking Union Medical College Hospital in China. The study enrolled patients aged 16 years and older receiving inpatient care and their clinicians. Patient recruitment was conducted from March 2023 to November 2023. Assessments In addition to demographic and clinical characteristics, this study employed two validated structured assessment tools to evaluate treatment expectations among patients and their clinicians: the Hospitalized Patients’ Expectations for Treatment Scale-Patient version (HOPE-P) and its counterpart, the Hospitalized Patients’ Expectations for Treatment Scale-Clinician version (HOPE-C). Results A total of 233 patients (mean [SD] age, 52.3 [15.1] years; 108 [46.4%] female) along with their clinicians, who numbered 75 in total were enrolled in this study. The distribution of total scores for HOPE-P and HOPE-C displayed similar patterns, with most scores concentrated in the higher range (above 50% of the full score). The mean HOPE-P total score was higher than that of HOPE-C (mean [SD] score, 38.78 [4.86] vs 37.49 [4.32]; t = 3.12, P = 0.002). In Dimension 2, the HOPE-P score was higher than HOPE-C (23.67 [3.20] vs 21.72 [3.03]; t = 6.98, P < 0.001). However, in Dimensions 1 and 3, HOPE-P scored lower than HOPE-C (13.37 [2.44] vs 13.84 [1.73]; t = -2.384, P < 0.018; 1.74 [1.14] vs 1.94 [1.00]; t = -2.00, P = 0.047). Certain demographic and clinical characteristics led to variations in patients’ treatment expectations, including marital status, monthly family income, and smoking history. Conclusions and relevance This cross-sectional study revealed significant differences between patients’ and doctors’ treatment expectations. Notably, it highlighted the need for clinicians to focus on rationalizing patients’ expectations concerning treatment outcomes. Trial Registration Chinese Clinical Trial Registry Identifier ChiCTR2300075262.